Preparation and functionalization of zinc oxide nanoparticles with polymer microgels for potential catalytic applications. Issue 2 (1st February 2022) - Khan, Abbas; Ullah, Muhammad; Humayun, Muhammad; Shah, Nasrullah; Chang, Boon Peng; Yaseen, Muhammad
Abstract: The preparation, functionalization and catalytic application of ZnO nanoparticles have been systematically carried out. In the first step, the virgin ZnO nanoparticles were prepared from Zn(CH3 COO)2 ·2H2 O solution in an alcoholic medium using the liquid precipitation approach. To form a new type of (zinc oxide)-(chitosan)-poly(N-isopropylacrylamide-acrylic acid), abbreviated as [ZnO-CS-P(NIPAAm-AA)], hybrid polymer microgels; ZnO particles were loaded to the chitosan based polymer microgels. Both the pure and hybrid ZnO materials, so obtained, were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), UV–visible spectroscopy and dynamic light scattering (DLS). For the hybridization purpose, the CS-P(NIPAAm-AA) polymeric gels were prepared by free-radical polymerization. Physicochemical behavior of these hybrid microgels was found responsive to external stimuli such as temperature and pH. In order to trace the hydrodynamic size of the ZnO, microgel, and ZnO-microgel hybrid system, DLS were also performed. From the overall results, the formation of ZnO nanoparticles with an average particle size of ≈ 35-42 nm having some irregularity in structure was confirmed. Likewise, SEM results show that pure CS-P(NIPAAm-AA) microgel particles are spheroid in shape with a smooth surface while the ZnO-CS-P(NIPAAm-AA) hybrid microgel particles look somewhat rough and having irregularity in their overall shape/structure. The fine particles of virgin ZnO and their hybrid with microgel was used for the catalytic reduction of 4-nitrophenol into 4-aminophenol and the results of both materials were compared. In addition, the kinetics of this catalytic reduction has also been summarized. The factors those influence the reduction rate of 4-nitrophenol in the presence of inorganic-organic hybrid materials have also been discussed and it was also found that the ZnO-microgel hybrid samples acted as a better catalytic agent compared to the ZnO or microgel alone. Graphical Abstract: UF0001 Preparation and Functionalization of Zinc Oxide Nanoparticles with Polymer Microgels for Potential Catalytic Applications